KARAKTERISTIK KESULITAN PADA PEMBELAJARAN DARING SISWA MADRASAH ALIYAH ISLAMIYAH PONTIANAK - Siti Khotimah; Indri Astuti; Amallia Putri (Universitas Tanjungpura, 2022)
AbstractThe purpose of this research is to determined the characteristics of learners which has learning difficulties when online learning. This study was conducted using an qualitative research method with descriptive approach. Informants data sources used in this study were three students class X Madrasah Aliyah Islamiyah Pontianak who were determine by using purposive sampling technique. The resarch method used an intrinsic case study and data collection techniques in the form of interviews, observation and documentation studies. Analysis of data collection using the interactive model of Miles and Huberman which consists of three stages, namely reduction, presentation and conclusion. The results of this research showed that the students characteristics who experience study difficulties during the online learning process include feeling unmotivated in participating in online learning, not focusing on online learning and difficulties in understanding the subject matter. Thus, it was concluded that the characteristics of learners who have difficulty online learning are marked by changes in student learning motivation who become less enthusiastic in the learning process.Keywords: Characteristics, Online Learning Difficulties, Students